Promoting safe-sun behaviors in outdoor workers - Entringer, Aaron Christopher (Kansas State University, 2019)
Sun exposure, with its link to the development of skin cancer and other health issues, can be a serious health hazard. In particular, those who primarily work outdoors and are consistently exposed to the sun’s rays are at elevated risk for such health problems. Previous research efforts have focused on appealing to these outdoor workers to practice sun protection behaviors, such as using sunscreen, wearing a hat, or wearing items of clothing that reduce the amount of skin exposed to the sun’s rays. In an effort to promote such sun protection behaviors, study 1 used a 3 X 2 between-subjects design to investigate the effects of tailored messaging and the inclusion of content regarding financial consequences of skin cancer on outdoor workers’ intention to practice sun protection behaviors. Results from study 1 suggest that tailored messaging was equally as effective as targeted messaging, with both being more effective than generic messaging. This finding indicates that some degree of personalization is necessary when promoting safe sun practices to outdoor workers, but that tailoring to individuals is unnecessary. Additionally, the inclusion of financial content in messaging resulted in participants having greater intentions to practice sun protection behaviors. In study 2, managers and supervisors of outdoor workers were studied in determining the importance of consequences related to employee well-being and financial consequences for employers when it comes to encouraging sun protection behaviors in their employees. Using a four-level between-subjects intervention, it was found that managers and supervisors who received messages that emphasized the financial consequences of employee sun exposure had greater intentions to encourage sun protection behaviors in their employees than those who received a message focused solely on employee well-being. This finding indicates that employers may be most concerned with financial consequences when it comes to promoting employee health. Together, studies 1 and 2 provide insight into the most effective methods for promoting sun protection for outdoor workers.
Keywords: Sun Protection; Skin Cancer; Outdoor Workers; Tailoring; Persuasion